2020
DOI: 10.1371/journal.pmed.1003168
|View full text |Cite
|
Sign up to set email alerts
|

Consistent sleep onset and maintenance of body weight after weight loss: An analysis of data from the NoHoW trial

Abstract: Background Several studies have suggested that reduced sleep duration and quality are associated with an increased risk of obesity and related metabolic disorders, but the role of sleep in long-term weight loss maintenance (WLM) has not been thoroughly explored using prospective data. Methods and findings The present study is an ancillary study based on data collected on participants from the Navigating to a Healthy Weight (NoHoW) trial, for which the aim was to test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…We found that a substantial proportion of adults attempting weight loss keep irregular sleeping schedules. Since prior research provides evidence that sleep regularity is associated with obesity and weight loss maintenance [ 37 , 38 ], weight loss interventions should be aware of the potential for poor sleep regularity in their population and should measure, and potentially address, irregular sleep patterns.…”
Section: Discussionmentioning
confidence: 99%
“…We found that a substantial proportion of adults attempting weight loss keep irregular sleeping schedules. Since prior research provides evidence that sleep regularity is associated with obesity and weight loss maintenance [ 37 , 38 ], weight loss interventions should be aware of the potential for poor sleep regularity in their population and should measure, and potentially address, irregular sleep patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Objectively measured sleep was also collected using the Fitbit Charge 2. Sleep duration and sleep onset was assessed across the 14 days close to baseline examinations using a previously described approach ( 35 , 36 ). Mean daily sleep duration was calculated and included in analyses as a categorical variable: <6, 6–<7, 7–<8, 8–<9, and ≥9 hours.…”
Section: Methodsmentioning
confidence: 99%
“…To get associations independently of self-reported stress, sensitivity analyses additionally adjusted for the PSS were conducted. Moreover, since stress is closely related to sleep ( 39 ), and we have previously shown an association between sleep onset variability and weight regain among the NoHoW participants ( 35 ), sensitivity analyses were conducted adjusting for sleep duration and sleep onset variability. Analyses adjusted for hair washing frequency and use of hair dye were conducted as well, although the evidence for potential influence on HCC from these factors is inconsistent ( 21 , 40 ).…”
Section: Methodsmentioning
confidence: 99%
“…Current evidence suggests that acute bouts of exercise [74,75] and chronic exercise training [74][75][76] improve subjective sleep quality and objectively derived measures of sleep. Because both sleep quality and sleep duration have been linked to body weight regulation [77][78][79][80], it is possible that sleep is a mediator in the relationship between exercise and weight loss. Below we review existing literature on whether the effect of acute and chronic exercise on parameters of sleep is dependent on time of day.…”
Section: Effect Of Exercise Timing On Sleepmentioning
confidence: 99%